Association of Tumor Necrosis Factor-Alpha -308 G>A Polymorphism With Rheumatoid Arthritis in Two North Indian Cohorts - Priyanka RAINA,; Kawaljit MATHAROO,; Ajay KUMAR,; Priyanka SARANGAL,; Rubina SHARMA,; AJS BHANWER, (Archives of Rheumatology, 2014)
Objectives: This study aims to analyze the role of tumor necrosis factor-alpha -308 G>A polymorphism with susceptibility to rheumatoid arthritis (RA) in population of Punjab, Jammu and Kashmir. Patients and methods: A total of 251 blood samples were collected comprising 131 samples from Punjab (cohort 1) (40 RA positive and 43 RA negative and 48 healthy controls) and 120 samples from Jammu and Kashmir (cohort 2) (44 RA positive, 36 RA negative and 40 controls). Genotyping was based on amplification refractory mutation system-polymerase chain reaction, followed by agarose gel electrophoresis. Results: In both the cohorts, higher percentages of females were observed to be affected than males (67.8% in cohort 1 and 65% in cohort 2). The frequency of A-allele in cohort 1 and cohort 2 was 10.2% and 18.8% in cases, respectively, while it was 7.9% and 23.2% in controls, respectively. In cohort 2, sex-specific association in males with RA was observed, whereas no similar association was observed in cohort 1. Rheumatoid arthritis patients presented with lower values for profiles of adiposity, suggesting association of weight loss with progression of RA. Conclusion: Tumor necrosis factor-alpha -308 G>A polymorphism does not seem to play a significant role in predisposition to RA in North Indian population of Punjab, Jammu, and Kashmir.